EXIT INTERVIEWS: A MIRROR FOR THE EMPLOYER - Mokibelo, Eureka (European Journal of Human Resource, 2020)
Purpose: This paper investigated the extent to which employers in Botswana use exit interviews to reflect on the feedback provided by the leaving employees for improvement. It is essential in any organization, division or company to reflect on its objectives, goals, achievements and setbacks for its growth and development. Employees may choose to quit their unpleasant jobs or express concern in an effort to improve the situation. Methodology: The study adopted mixed method approach and employed in-depth interviews and questionnaires for data collection. The informants of this study were the University of Botswana academic employees who previously had other jobs before being employed by the university. Findings: Findings indicated that exit interviews could assist in improving the performance and growth of an organization, division or company. The leaving employee could reveal information that could contribute towards the strengths and development of a company, division or an organization. It is anticipated that the results might significantly contribute to companies and organization in Botswana that could otherwise overlook the importance of exit interviews to reduce exit.